2016
DOI: 10.1080/02705060.2016.1248506
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of bacterial abundance and the related environmental factors in large shallow eutrophic Lake Taihu

Abstract: In aquatic ecosystems, estimation of bacterial abundance (BA) is intimately connected to the development of an understanding of the role of bacteria in microbial food webs. Flow cytometry (FC) can rapidly calculate BA, but to date mostly has been applied in marine waters with limited use in shallow eutrophic lakes because of the abundant organic and inorganic matter. To seek the best compromise between precision and the clarity for the differentiation of bacteria from other submicron-sized particles and colloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…In our study, water temperature had a significant positive influence on the relative abundance of bacteria and Pseudomonas in particular. This result was consistent with previous analyses [6,8,11,21], in that the increase of bacterial abundance significantly correlates with higher water temperature. Our results also indicated that TAN concentration was significantly negatively correlated with Pseudomonas population, while insignificant correlations between the relative abundance of Pseudomonas with all other environmental parameters were shown.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, water temperature had a significant positive influence on the relative abundance of bacteria and Pseudomonas in particular. This result was consistent with previous analyses [6,8,11,21], in that the increase of bacterial abundance significantly correlates with higher water temperature. Our results also indicated that TAN concentration was significantly negatively correlated with Pseudomonas population, while insignificant correlations between the relative abundance of Pseudomonas with all other environmental parameters were shown.…”
Section: Discussionsupporting
confidence: 93%
“…Deterioration of environmental conditions has led to significant economic losses [5]. Changes in environmental parameters have been shown to change the structure of bacterial communities in the water of aquaculture systems [6,7,8,9], and bacteria have been found to play roles in remediating polluted and contaminated water [10] and are correlated with water quality [11]. Information is lacking regarding environmental effects on the relative abundance of bacteria for the monitoring of water quality in shrimp ponds.…”
Section: Introductionmentioning
confidence: 99%
“…The samples were analyzed on a FACSC JAZZ flow cytometry (BD Bioscience, San Jose, CA, USA) using FACS software (BD Bioscience), detailed in Gong, et al . 36 .…”
Section: Methodsmentioning
confidence: 99%
“…500 μl of the sample was diluted 10-fold with ultrasonic processing (separate bacteria) for 10 min, and then filtered through a 48 µm mesh net. Finally, 1 ml of each sample was immediately analyzed on a FACSC JAZZ flow cytometry using FACS software 36 .…”
Section: Methodsmentioning
confidence: 99%
“…Smaller particles are usually collected and separated by filtration using filters of different pore sizes. At least seven different filter pore sizes have been used to separate PA from FL bacteria: 20 µm (Worm and Søndergaard, 1998), 10 µm (Becquevort et al, 1998;Becquevort and Smith, 2001;Riemann and Winding, 2001;Arnosti et al, 2012), 8.0 µm (Acinas et al, 1997(Acinas et al, , 1999, 5.0 µm (Selje and Simon, 2003;Allgaier and Grossart, 2006;Parveen et al, 2011;Rösel et al, 2012;Tang et al, 2015;Zhao et al, 2017;Hu et al, 2020), 3.0 µm (Crump et al, 1998(Crump et al, , 1999Herfort et al, 2017;Wang et al, 2020), 1.0 µm (Hollibaugh et al, 2000;Zhang et al, 2007), and 0.8 µm (Mevel et al, 2008;Ghiglione et al, 2009). Another method for collecting and separating smaller particles is centrifugation, which has been used in the studied of PA and FL assemblages in turbulent rivers and lakes (Böckelmann et al, 2000;Tang et al, 2009Tang et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%